1986
DOI: 10.1029/jd091id04p05189
|View full text |Cite
|
Sign up to set email alerts
|

Speciation, photosensitivity, and reactions of transition metal ions in atmospheric droplets

Abstract: Dissolved transition metal ions (TMI) are common constituents of atmospheric droplets. They are known to catalyze sulfur oxidation in droplets and are suspected of being involved in other chemical processes as well. We have reviewed the relevant equilibrium constants and chemical reactions of the major TMI (iron, manganese, copper, and nickel), their ability to form complexes in aqueous solution, and their potential involvement in photochemical processes in atmospheric droplets. Among the results are the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(61 citation statements)
references
References 120 publications
0
61
0
Order By: Relevance
“…Weschler et al (1986) considered the chelating ability of various ions to Cu, Fe and Mn in raindrops. The authors found that for Cu, SOi-and SOi-are probably the most important ligands after water.…”
Section: Methodology -Cu Molalitiesmentioning
confidence: 99%
“…Weschler et al (1986) considered the chelating ability of various ions to Cu, Fe and Mn in raindrops. The authors found that for Cu, SOi-and SOi-are probably the most important ligands after water.…”
Section: Methodology -Cu Molalitiesmentioning
confidence: 99%
“…The soluble Fe(III) may then be photoreduced to Fe(II). Graedel et al (1986), Weschler et al (1986), and Faust and Hoigne (1990) suggested that at a pH of -2.5-5, typical of cloud and rain droplets, the following reaction may produce Fe(II): hv [Fe(OH) (H20)J2+ H20 -+…”
Section: A Final Region Is the High Latitude Southernmentioning
confidence: 99%
“…Thus it has been suggested that dissolved metals in wetted aerosols or rainwater occur as the aquated free ions and in complexes with chloride, sulfite, sulfate and hydroxide ions. Weschler et al (1986) have shown, using critical stability constants, that whereas Mn II and Ni II occur almost entirely as the hexaqua ion, Fe III can also occur in atmospheric droplets as [Fe(OH)(H 2 O) 5 ] 2ϩ , [Fe(OH) 2 (H 2 O) 4 ] ϩ and [Fe(SO 3 )(H 2 O) 4 ] ϩ with the partitioning being a function of pH. More recent studies have pointed to the importance of specific low molecular weight organic compounds in both aerosols and rain in controlling the speciation of iron.…”
Section: ϫmentioning
confidence: 99%